PERANCANGAN DESIGN WEBSITE INKUBATOR BISNIS PRIMAKARA MENGGUNAKAN METODE DESIGN THINKING DAN KANBAN BOARD - Tiawan Tiawan; Made Artana; I Kadek Adi Gilang Pratama; I Komang Adi Galang Permana (Program Studi Informatika Universitas Teknologi Sumbawa, 2023)
The design of the Primakara business incubator website using Design Thinking, Branding, and Kanban Board methods aims to create a website that is attractive, easy to use and strengthens the Primakara brand. This process involves structured and iterative planning to ensure that the website meets the needs and expectations of users. The Design Thinking method ensures that the website planning process takes into account the needs and expectations of users. This is done by involving users in every planning stage, from problem understanding to solution validation. Branding ensures that the website presents Primakara as a business incubator that is professional, innovative, and has strong values. Branding also ensures that the website has a consistent appearance and strengthens Primakara's identity. The Kanban Board is used to monitor progress and manage tasks in website creation. This ensures that the manufacturing process runs efficiently and related tasks can be properly monitored and managed. The end result of this design is a website that has an attractive appearance, easy navigation, and quality content that presents Primakara as a leading business incubator. Thus, this website can help strengthen Primakara's existence as a trusted business incubator and assist in achieving its goals